World of Deacon Pobedov in Chekhov’s Novel «The Duel»: Laughter, Dialogue, Space (Proceedings of Southern Federal University. Philology, 2020)
This article deals with the study of the phenomenon of laughter, which is an important component and feature of the character of deacon Pobedov in Chekhov’s novel «The Duel». The deacon’s laughter, as a reaction to the words and actions of other characters, implements in dialogues when Pobedov acts as an observer of the act of communication. In this context, laughter should be considered as an assessment of a communicative event. The study shows that the deacon, being in the space of nature, loses laughter as a positive reaction. In this space, the deacon, on the one hand, in the internal dialogue acts as a dreaming and reflecting person, and, on the other hand, a person experiencing feelings of fear, despair, and excitement.Key words: Chekhov, «The Duel», deacon Pobedov, laughter, dialogue, space of nature.DOI 10.18522/1995-0640-2020-2-27-35